Investigating Internships in Architectural Education - Nehad Eweda (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Nowadays, as a response to the evolving complexities and emerging technologies of buildings, the practice of architecture is rapidly changing. In this regard, how should architectural education respond to these changes? Although the continuous endeavors of architectural schools to make their educational programs up-to-date and to simulate the environment of architectural practice, there is still a gap between academia and profession that requires offering a period of practical training to the students or what is called internships. In Egypt, one of the challenges facing architecture graduates is the high competitiveness within the relatively growing number of architectural schools and graduates as well. This research aims at investigating the common practices in implementing internships in architectural education. To achieve this aim, an analytical inductive methodology was adopted and supported by quantitative research that analyzed the practices of internships in a sample of twentyeight undergraduate architectural programs in Egypt, Middle East, and worldwide. This research is divided into four sections; the first section is an overview of the topic, the second documents the survey sample, methodology, and procedures, the third presents the findings of the survey, and finally, the fourth is the discussion.